Micropore Characteristics and Gas-Bearing Characteristics of Marine-Continental Transitional Shale Reservoirs in the East Margin of Ordos Basin - Yuanzhen Ma; Meng Wang; Ruying Ma; Jiamin Li; Asiya Bake; Yadi Shan (Adsorption Science & Technology)
In order to deeply study the exploration potential of Carboniferous-Permian marine-continental transitional shale reservoirs in the Ordos Basin, the shale samples from well Y1 in the central-southern part of the Hedong Coalfield were used as the research object. The organic geochemical test, scanning electron microscope, X-ray diffraction, and high pressure mercury injection and low-temperature nitrogen adsorption experiments have studied the microscopic characteristics and gas content characteristics of shale reservoirs. The results show that the organic matter type of the sample is type III; the TOC content ranges from 0.28% to 16.87%, with an average of 2.15%; Ro is from 2.45% to 3.36%, with an average value of 2.86%; the shale pores in the study area are well developed, containing more organic pores and intergranular pores of clay minerals. Based on the two-dimensional SEM image fractal theory to study different types of pores, the fractal dimension of shale pore fracture morphology is between 2.34 and 2.50, and the heterogeneity is moderate. The high-pressure mercury intrusion experiment characterizes the pore size distribution of shale macropores and transition pores. The pore diameters are mostly nm-scale. Transition pores are the main pores of the shale in the study area. Based on the characteristics of the pore structure, the adsorption capacity and gas content of CH4 in shale reservoir were analyzed by methane isothermal adsorption and gas content experiments. The results showed that the pore volume and specific surface area were positively correlated with clay mineral content, TOC, and RO, but negatively correlated with the quartz content. In clay minerals and brittle minerals, pore volume and specific surface area are positively correlated with illite content and negatively correlated with the quartz and kaolinite content. The measured total gas content and desorbed gas content are significantly positively correlated with TOC, but are weakly positively correlated with the quartz and illite content. This study finely characterizes the physical properties, micropore characteristics, gas-bearing characteristics, and influencing factors of shale reservoirs, which has certain theoretical guiding significance for the research and development of coal-measure shale in the Ordos Basin.